FCJ-176 a skeuomorphic cinema: film form, content and criticism in the ‘post-analogue’ era - Fleming, David H.; Brown, William (Open Humanities Press, 2015)
Adopting an archaeological approach to digital cinema that helps us to recognise both the old in the new, and the new in the old, this article argues that a 'skewed' critical concept of the 'skeuomorph' can help us move beyond notions of remediation, convergence, and simulacra to better understand the complex entanglement of the familiar and the novel that currently defines contemporary cinematic form, content, and criticism. Using different examples to make our case, we maintain that audiences and filmmakers alike have not yet fully adapted to best read or understand the newly emerging digital forms, and are thus consequentially 'not quite seeing them for what they are, and always unconsciously trying to understand them in terms of the old and familiar' (Gessler 1998). By drawing attention to several contemporary blind spots, our detoured notion of the skeuomorph aims to make the new and novel features of digital film palpable.